2004
DOI: 10.1038/sj.onc.1207899
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cancers of the breast, endometrium and ovary

Abstract: A central epidemiological feature of cancers of the breast, endometrium and ovary is the sharp slowing down in their rate of increase with age around the time of menopause. The incidence of these tumors by the age of 70 years would be between fourfold and eightfold increased if the rapid increase with age seen in young women continued into old age. These phenomena can be explained by the different effects of ovarian hormones on cell division rates in the relevant tissues. Models of these effects provide a plau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
1
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 95 publications
(92 reference statements)
3
113
1
4
Order By: Relevance
“…Estrogen appears to act as a carcinogen by stimulating cell proliferation in estrogen-responsive tissues (1). Progesterone may also play a role by opposing estrogen (1,13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogen appears to act as a carcinogen by stimulating cell proliferation in estrogen-responsive tissues (1). Progesterone may also play a role by opposing estrogen (1,13).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical information was obtained from their medical records. Although hormone therapy influences endometrial divisions (1), and some of the women received exogenous estrogen, this information was not uniformly documented and therefore not analyzed in this study. Glands free of stroma were isolated with a procedure originally developed for the colon (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, serum CA15-3 level showed a non-significant increase within elderly menopause patients with breast cancer, in contrast to what was reported by Dehaghani et al, (2007) who found statistically significant values. Aging and menopause usually disturb immunity and hormonal status (Pike et al, 2004;Rymer & Morris, 2000). So screening this marker is recommended for females above forty years since Jordanian develop breast cancer at a much younger age (median age is 51) than women in Western countries (median age is 65) (Jordan breast cancer program, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…CA15-3 level increased in 10% stage I breast cancer disease, 20% stage II disease, 40% stage III disease, and 75% with stage IV disease (Duffy 2006). Elevated levels of this biomarker were detected among certain benign diseases, primary breast carcinoma (Coveney et al, 1995) and in patients with advanced adenocarcinomas (Anonymous, 1996;RESEARCH COMMUNICATION among females and increase the chance of breast cancer development (Crump et al, 2000;Rymer & Morris, 2000;Pike et al, 2004;Hulka & Moorman;2008), at the same time, serum CA15-3 level showed a significant increase within elderly menopause patients with breast cancer (Dehaghani et al, 2007). The aim of this study is to determine serum level of the tumor marker CA15-3 among Jordanian healthy, benign breast lesions and breast cancer females, as well as to highlight relationship between CA15-3 level with cancer onset age, menarche, menopause, body mass index (BMI), oral contraceptives (OCP), hormonal therapy (HT), tumor grade, stage and hormonal receptor status among breast cancer females.…”
Section: Introductionmentioning
confidence: 99%